1995
DOI: 10.1007/bf00194695
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal autonomic nerve tumours and their separation from other gastrointestinal stromal tumours: an ultrastructural and immunohistochemical study of seven cases

Abstract: Gastrointestinal stromal tumours (GIST) represent a heterogeneous group whose classification frequently requires ultrastructural and immunohistochemical studies. In a retrospective study of the ultrastructural findings of 24 gastrointestinal stromal tumours, whose light microscopic study has yielded ambiguous results and in which accurate diagnosis had required ultrastructural support, seven were found to have the characteristics of gastrointestinal autonomic nerve (GAN) tumours. In all of them the diagnosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 19 publications
(28 reference statements)
1
31
0
1
Order By: Relevance
“…Information on NSE reactivity in GISTs is limited [7]. We found that over 80% of GISTs were NSE positive and that approximately 30% of non-gastric tumors were S-100 positive, suggesting the possibility of neural differentiation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Information on NSE reactivity in GISTs is limited [7]. We found that over 80% of GISTs were NSE positive and that approximately 30% of non-gastric tumors were S-100 positive, suggesting the possibility of neural differentiation.…”
Section: Discussionmentioning
confidence: 88%
“…We found that over 80% of GISTs were NSE positive and that approximately 30% of non-gastric tumors were S-100 positive, suggesting the possibility of neural differentiation. Gastrointestinal autonomic nerve tumors (GANTs) are described as distinctive entities that differ from other mesenchymal tumors of the gastrointestinal tract [2,57], and most have been reported as immunoreactive for vimentin, NSE, and occasionally S-100 [7]. However, recent studies have suggested that GANTs are not a separate entity because they share a molecular genetic identity with conventional spindle and epithelioid cell forms of GIST [28].…”
Section: Discussionmentioning
confidence: 99%
“…)differentiate into smooth muscle cells, when ckit signaling is blocked [98]. Moreover, their malignant counterparts in GIST occasionally express either smooth muscle [99] or neuroendocrine [100] markers.…”
Section: T-icc: Uncommitted (Bipotential) Progenitor Cellmentioning
confidence: 99%
“…The common sites are stomach, small intestine and retroperitoneum [3,14,15,20], but a case of oesophageal GANT was recently reported [19]. The clinical symptoms vary, including an enlarging abdominal mass, abdominal pain and gastrointestinal bleeding [14,15,22].…”
Section: Discussionmentioning
confidence: 98%